Two new species of the treehopper genus Machaerotypus Uhler, 1896 from China (Hemiptera: Membracidae: Centrotinae) - Li, Feng-E.; Yang, Lin; Long, Jian-Kun; Chang, Zhi-Min; Chen, Xiang-Sheng (European Journal of Taxonomy, 2022)
Two new species of the treehopper genus Machaerotypus Uhler, 1896, M. stigmosus Li & Chen sp. nov. and M. nodulus Li & Chen sp. nov., are described and illustrated from Guizhou Province, China. A checklist and key to species of Machaerotypus are provided with a map of geographic distribution.